Wokół książki Poznański Czerwiec 1956. Z profesor Zofią Trojanowiczową rozmawia Wiesław Ratajczak - Trojanowiczowa, Zofia; Ratajczak, Wiesław (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
A conversation with professor Zofia Trojanowiczowa on the background and origin of Poznań 1956 protests . This was the first collection of essays and relations, and it was published in June 1981. A co-author of the book remembers the enthusiasm of revealing the truth about the workers’ uprising.